Coronavirus disease 2019 vaccination‐induced acute exacerbation in idiopathic pulmonary fibrosis. Issue 11 (12th October 2022) - Sugino, Keishi; Ono, Hirotaka; Saito, Mikako; Ando, Masahiro; Tsuboi, Eiyasu
Abstract: We report a rare case of acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) after coronavirus disease 2019 (COVID‐19) vaccination. Clinicians should be aware of this COVID‐19 vaccination‐induced AE in IPF Abstract : Here we report a rare case of acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) after coronavirus disease 2019 (COVID‐19) vaccination. Although, it is difficult to differentiate idiopathic AE from COVID‐19 vaccination‐induced AE, we suppose that vaccination can trigger AE of IPF characterized by a steroid‐responsive episode.